Celah Hukum dalam Asuransi Kecelakaan Kerja - Pratama, Din Eri; Syafaat, Muhammad Arif; Apriani, Rani (Jurnal Ilmiah Wahana Pendidikan, 2025)
The protection of workers who experience work accidents in Indonesia has been regulated in various regulations, such as Government Regulation Number 49 Year 2023 (PP49/23). However, in practice, there is still a legal vacuum that results in some workers, especially freelancers, not getting proper coverage. This study analyzes the case of a worker who suffered permanent disability due to a work accident, but did not receive appropriate compensation from the company. Using a juridical-normative approach and case analysis, this study finds that loopholes in the legal system and weak supervision mean that workers' rights are not fully met. Therefore, there is a need to revise policies and improve supervision mechanisms so that every worker, regardless of employment status, receives optimal legal protection